"Living apart together": moral frictions between two coexisting organ transplantation schemes. Issue 6 (29th May 2008) - Hilhorst, M T
Abstract : Cadaveric transplantation and living transplantation exist side by side. Both practices help to alleviate organ need. They provide us with two separate moral schemes. Is it rational to keep them apart? The cadaveric system is organised along strict, impartial lines, while the living system is inherently partial and local. The ethical justification for this partial scheme seems to be that it merely supplements the cadaveric scheme: partial transplants do not come at the expense of cadaveric impartiality, but in fact significantly reduce the waiting time for patients on the list for a cadaveric transplant. This seemingly peaceful coexistence is challenged by new initiatives, among them living donation list exchange, and also the LifeSharers initiative, leading to practices that undermine cadaveric impartiality. Should we bemoan this fact, or should we move on towards a new balance in the relationship between cadaveric and living transplantation practices, towards a new moral weighing of impartial and partial values? I argue, against the background of a rapid growth of living donations, that we have good, ethical reasons—not only utilitarian ones—for giving the value of partiality a more prominent place in our policies.